2001
DOI: 10.1104/pp.010386
|View full text |Cite
|
Sign up to set email alerts
|

A Chloroplast Protein Homologous to the Eubacterial Topological Specificity Factor MinE Plays a Role in Chloroplast Division

Abstract: We report the identification of a nucleus-encoded minE gene, designated AtMinE1, of Arabidopsis. The encoded AtMinE1 protein possesses both N-and C-terminal extensions, relative to the eubacterial and algal chloroplast-encoded MinE proteins. The N-terminal extension functioned as a chloroplast-targeting transit peptide, as revealed by a transient expression assay using an N terminus:green fluorescent protein fusion. Histochemical ␤-glucuronidase staining of transgenic Arabidopsis lines harboring an AtMinE1 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(54 citation statements)
references
References 60 publications
2
52
0
Order By: Relevance
“…Consequently, constriction is confined to the midcell in the presence of MinC, MinD, and MinE (de Boer et al 1989). Earlier work demonstrated that AtMinE 1 targeted chloroplasts, and that overexpression of the AtMinEl gene reduced chloroplast number, but resulted in chloroplast enlargement (Itoh et al 2001). These results demonstrated the critical role of AtMinEl in chloroplast division.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…Consequently, constriction is confined to the midcell in the presence of MinC, MinD, and MinE (de Boer et al 1989). Earlier work demonstrated that AtMinE 1 targeted chloroplasts, and that overexpression of the AtMinEl gene reduced chloroplast number, but resulted in chloroplast enlargement (Itoh et al 2001). These results demonstrated the critical role of AtMinEl in chloroplast division.…”
supporting
confidence: 59%
“…This fragment was digested with BamHI and SacI (sites indicated by underlines) and ligated in the antisense orientation into the same restriction sites of pBI121 (TOYOBO, Tokyo, Japan). This plasmid was used for stable transformation of Arabidopsis with Agrobacterium tumefaciens as described previously (Itoh et al 2001). …”
Section: Construction Of Transgenic Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional homologue of FtsZ that is distinct from FtsZ1 and FtsZ2, but is still related to cyanobacterial FtsZs, is also present in plastids of primitive algae. Homologues of cyanobacterial MinD and MinE proteins are found in plants, and are required for the proper localization of plastid Z rings in Arabidopsis thaliana 108,109 , which indicates that the function of MinD and MinE in the spatial regulation of plastid Z rings has been conserved. Nevertheless, no homologues of MinC have been found in plants, so the factor that negatively regulates FtsZ assembly through MinD in plastids is not yet known.…”
Section: Ftsz and Organelle Division Plastid Divisionmentioning
confidence: 99%
“…The first step seems to be the polymerization of AtFtsZ at the division site, forming the Z-ring , probably stabilized by ARC6, a DnaJ domain protein (Vitha et al, 2003). Like in bacteria (Justice et al, 2000), establishment of the proper division site is mediated by AtMinD and AtMinE (Colletti et al, 2000;Itoh et al, 2001). Then, sequential assembly of the inner and outer plastid division rings (PD ring) follows.…”
Section: Introductionmentioning
confidence: 99%